Analysis of Implementation of Patient Referral Program at Naili DBS Hospital Padang - Tuti Gusra; Rima Semiarty; Ida Rahmah Burhan (Syntax Corporation, 2022)
ReferBack Program is one of BPJS health flagship program. The implementation of the ReferBack Program will benefit many parties, be it patients, FKTP, or FKTL. The high referral rate is not balanced with the referback number which makes the buildup of patients in the hospital. Data from BPJS Padang in 2020 the totally of patients referred to FKRTL in 2019, and 2020 was 409,567 and 204,886 while the ReferBack figures were only 4,620 and 1,806 which showed referral rates of only 1.1% and 0.5%, meaning that from 100 visits to FKRTL there are as many as 1-2 patients who are then referred back to FKTP. This study aims to see the Refer Back Program in Naili DBS Hospital which is viewed from the input, processes, and outputs. This Research is qualitative research using system approach methods. The research was conducted at Naili DBS Padang Hospital in February - June 2021. The implementation of referback program at Naili DBS Padang Hospital in 2021 has not been carried out properly. In the input component there is no specific flow for patients with potential diagnosis of PRB. Input personnel are not competent, socialization to patients does not exist yet and has not optimal monitoring and evaluation from the leadership so that the implementation of the referback program has not been carried out in accordance with the target set by BPJS.